SPEECH ACTS AND APPLICATION OF TEACHER COOPERATION PRINCIPLES IN INDONESIAN LANGUAGE LEARNING: TINDAK TUTUR DAN PENERAPAN PRINSIP KERJA SAMA GURU DALAM PEMBELAJARAN BAHASA INDONESIA - Yetty Morelent; Syofiani Syofiani; Romi Isnanda; Wiwik Sundari (Jurnal Kata, 2023)
A this research aims to describe the form and types of speech acts, as well as a description of the principle of cooperation in teacher speech in the Indonesian language learning process at SMAN Padang City. This type of research is qualitative research with descriptive methods, while the research data is all Indonesian language teacher speech which contains the forms and types of speech acts as well as the principles of cooperation. Data collection techniques are carried out through the observation and recording stages. Data analysis techniques are: (1) Transcribing the speech of teachers who teach Indonesian; (2) classifying the types of teacher speech and the principles of cooperation between teachers who teach Indonesian; (3) interpreting the data found, (4) drawing conclusions, and making reports related to teacher speech acts and the application of the principle of cooperation. Based on the research results, it can be concluded that speech acts and the principle of cooperation are interconnected because to find out teachers adhere to the principle of cooperation seen from the meaning of the speech spoken by the teacher to the students.